A cerium concentrated heavy fermion? - Sereni, Julian Gustavo R.; Nieva, Gladys L.; Olcese. G. L.; Herr, A.; Kappler, J. P. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Sereni, Julian Gustavo R. Comisión Nacional de Energía Atómica; Argentina